2013
DOI: 10.1007/s12185-013-1423-8
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo activation of angiogenic property in human peripheral blood-derived monocytes by thrombopoietin

Abstract: Human peripheral blood mononuclear cells (PB-MNCs) have angiogenic properties, which make them promising cells for use in angiogenic therapy approaches in regenerative medicine. To explore an efficient method for expanding pro-angiogenic cells from PB-MNCs, we developed a novel serum-free culture system composed of X-VIVO15 medium supplemented with vascular endothelial growth factor, basic fibroblast growth factor, and thrombopoietin (TPO). Using this ex vivo culture, we obtained floating spheres composed main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…CD133 + cells are going to be used for other diseases in the future as well as in the clinical study of acute myocardial infarction that is now underway : the healing of diabetic ischemic ulcers , spinal cord regeneration , sciatic nerve defects , and bone healing . Early EPCs from CD133 + cells were shown to powerfully promote tissue regeneration by cultivation , like early EPCs that are differentiated from PBMCs or CD11b + cells . MMP9 + cells from CD133 + cells produced much more IL‐8 than that produced by MMP9 + /MMP2 + cells from PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…CD133 + cells are going to be used for other diseases in the future as well as in the clinical study of acute myocardial infarction that is now underway : the healing of diabetic ischemic ulcers , spinal cord regeneration , sciatic nerve defects , and bone healing . Early EPCs from CD133 + cells were shown to powerfully promote tissue regeneration by cultivation , like early EPCs that are differentiated from PBMCs or CD11b + cells . MMP9 + cells from CD133 + cells produced much more IL‐8 than that produced by MMP9 + /MMP2 + cells from PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Nucera et al () proposed that the generation of proangiogenic Mϕ from embryonic stem cells may provide a source of therapeutic cells for the treatment of ischemia, injured tissues, and chronic wounds. Both CD11b + cells and MNCs have been shown to markedly promote tissue regeneration by cultivation (Kawamoto et al, ; Masuda et al, ). During this process of differentiation, the cell surface expression of MMP‐2/9 may be one of the useful markers for proangiogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al showed that TPO treatment could reduce myocardial infarct size and apoptosis following ischemia-reperfusion through multiple signaling pathways including JAK-2 and p42/44 MAPK as well as K (ATP) channels 21 . TPO also enhanced the correction of ischemia via promoting angiogenic response mediated by the increased platelet level 6 . The present study shows that after 2 hours ischemia followed by 22 hours reperfusion, the BBB permeability was massively increased, leading to severe brain edema and neurologic deficit, TPO intervention significantly reduced brain edema and neurologic deficit caused by ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…c-MPL) are expressed in various organs including heart and nervous system which indicates that TPO may have hematopoiesis-independent effects 5 . TPO can augment angiogenic response 6 , improve ventricular function and present protection against myocardial ischemia 7 . Besides its expression in hematopoietic system, TPO receptor (c-MPL) also located in the central nervous system, and can inhibit the apoptosis of nerve cells, through the activation of the PI-3K/AKT signal pathway 8 .…”
Section: Introductionmentioning
confidence: 99%